A better way to manage patients with fractured mandibles. Issue 1 (January 2022) - Kent, Samuel; Dawoud, Basim; Henry, Alasdair; Kumar, Dee; Blore, Chris; Jeffries, Chris; Geddes, Alan; Kyzas, Panos
Abstract : Introduction: Day case surgery (DCS) for patients with fractured mandibles offers financial and social benefits over emergency admission (EM). However, delayed initiation of prophylactic antibiotics and fixation may increase number of post-operative infections. We use a snapshot audit to demonstrate that DCS is not associated with increased complication rates at 30 days and show that this strategy reduces costs to the hospital. Methods: We carried out a trainee led collaborative snapshot audit of all mandible fractures presenting to participating UK OMFS departments between December 2020 and June 2021, which recorded information on demographics, mechanism, injury, treatment and included a 30 day follow up. Resource use and costs were calculated using a micro costing analysis of individual patient level data. Post operative complications were defined as any unplanned antibiotics or readmission. Results: Information was gathered from 41 centres on 947 patients with 1532 fractures of the mandible. Of these, 717 (76%) patients were managed surgically, with 65 (9.3%) as DCS. Postoperative complications occurred in 69 (9.6%). There was no correlation between management strategy and complications. Patients managed by DCS were older (mean 36 vs 30 years, p=0.001), more likely to be female (29%vs 16%, p=0.007), and less likely to have sustained their injury through interpersonal violence (45%vs 63% p=0.001). Median cost was £2595 in DCS, and £3346 in EM. Conclusions: DCS appears to be a safe and cost effective way of managing mandibular fractures, currently used in a small cohort of patients. Its wider application depends upon availability of DCS facilities and change in practice.